Validation study of the Parent Attitudes About Childhood Vaccines (PACV) questionnaire: the Malay version. Issue 5 (3rd May 2020) - Abd Halim, Haizlene; Abdul-Razak, Suraya; Md Yasin, Mazapuspavina; Isa, Mohamad Rodi
ABSTRACT: Vaccine hesitant parents are linked with re-emergence of vaccine preventable diseases, but evidence is scarce locally. The Parent Attitudes about Childhood Vaccines (PACV) questionnaire was validated and used in the USA to identify vaccine hesitant parents. This study aimed to adapt and translate the 15-item PACV questionnaire from English into the Malay language, and to examine its validity and reliability. The sample population was parents of children aged 0–24 months, recruited at an urban government health clinic between November 2016-June 2017. During content validation, two items from the "Behavior" subdomain were identified as items with formative scale and excluded from exploratory factor analysis (EFA) but retained as part of demography. A total of 151 parents completed the questionnaire with response rate of 93.3%. Test-retest reliability was tested in 25 respondents four weeks later and the intra-class correlation was between 0.53 and 1.00. EFA of the 13 items showed possibility of two to four factor domains, but three domains were most conceptually equivalent. Two of the domains were similar to the original and one factor was identified de novo. One item was deleted due to poor factor loading of < 0.3. Therefore, the validated final PACV-Malay consisted of 12 items framed within three-factor domains. The PACV-Malay was reliable with total Cronbach alpha of 0.77. In conclusion, the PACV-Malay is a valid and reliable tool which can be used to identify vaccine hesitant parents in Malaysia. Confirmatory factor analysis and predictive validity are recommended for future studies.